Outcome-Based Education: An approach for teaching and learning development - Abdul Karim, Noor Al-Huda; Yin, Khoo Yin (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
This conceptual paper attempts to provide an understanding of the importance of outcome-based education (OBE) approach for teaching and learning development. As a theory of education, OBE has certain beliefs and assumptions about learning, teaching and the systemic structures within these activities. The results of OBE approach are expressed in terms of individual student learning and they are expected to achieve the two long-term benefits : i) OBE is able to measure 'what the students are capable of doing‘ and ii) OBE goes beyond 'structured tasks‘ by demanding that students demonstrate their skills through more challenging tasks. The OBE system also can be benefited when the outcomes are used to guide instructional planning. In Malaysia, the OBE system is implemented by the Malaysia Quality Agency (MQA). The Agency holds the task to improve the quality of human capital in the country from three main aspects namely, knowledge, skills and attitude.